Sports supplement consumption in 316 federated female road cyclists - García-Durán, J.; González-Jurado, J. A.; Sánchez-Oliver, A. J. (Nutrients, 2024)
Although the extensive use of sports supplements (SSs) is prevalent among cyclists, this area has been poorly explored; in fact, no studies have been conducted on this topic regarding women cyclists to date. This descriptive, cross-sectional study, which included 316 federated female road cyclists, aimed to analyze SS consumption patterns in relation to scientific evidence and various categories. SSs were categorized according to the groups and subgroups established by the Australian Sport Institute (AIS, 2023) based on the level of evidence supporting their use. The analysis found that 85.1% of the female road cyclists surveyed used SSs, with an average consumption of 7 ± 6 supplements per individual. Pharmacies (60.8%), dietitian-nutritionists (58.9%), and health status (60.1%) were the primary purchase location, source of information, and reason for use, respectively. The most frequently consumed supplements were sports bars (77.5%), sports gels (61.4%), and caffeine (49.1%). Significantly, 80% of the ten most commonly used supplements were from the group with the highest evidence level, as classified by the AIS, with an average intake of 5 ± 3 supplements per cyclist. In summary, the use of SSs is prevalent among female road cyclists, with reliable sources for both purchasing and obtaining advice on supplements.